Resource and Revenue Sharing with Coalition Formation of Cloud Providers: Game Theoretic Approach - Niyato, D.; Vasilakos, A. V.; Zhu Kun (2011 11th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2011)
In cloud computing, multiple cloud providers can cooperate to establish a resource pool to support internal users and to offer services to public cloud users. In this paper, we study the cooperative behavior of multiple cloud providers. The hierarchical cooperative game model is presented. First, given a group (i.e., coalition) of cloud providers, the resource and revenue sharing of a resource pool is presented. To obtain the solution, we develop the stochastic linear programming game model which takes the uncertainty of internal users from each provider into account. We show that the solution of the stochastic linear programming game is the core of cooperation. Second, we analyze the stability of the coalition formation among cloud providers based on coalitional game. The dynamic model of coalition formation is used to obtain stable coalitional structures. The resource and revenue sharing and coalition formation of cloud providers are intertwined in which the proposed hierarchical cooperative game model can be used to obtain the solution. An extensive performance evaluation is performed to investigate the decision making of cloud providers when cooperation can lead to the higher profit.